2003
DOI: 10.1002/ca.10064
|View full text |Cite
|
Sign up to set email alerts
|

Force‐length characteristics of the in vivo human gastrocnemius muscle

Abstract: In this study, the force-length characteristics of the in vivo medial (GM) and lateral (GL) heads of the human gastrocnemius muscle were estimated from measurements in eight healthy male subjects. This involved: 1) dynamometry-based measurements of the moment generated during maximal isometric plantar flexion; 2) ultrasound-based measurements of fascicular length and pennation angle; and 3) ultrasound-based calculations of moment arm lengths. All measurements were taken over the ankle angle range from 20 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
151
2
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(183 citation statements)
references
References 43 publications
19
151
2
5
Order By: Relevance
“…This is in stark contrast to findings by Kawakami et al (1998) who reported in vivo ultrasound pennation angles of 31±6° for the LG at MVC, considerably different than the smaller values used by Bogey et al, (2005). The average pennation angle for the male subjects in our study was 22°; identical to the in vivo value reported by Maganaris (2003). Differences between cadaver and in vivo measures of muscle architecture for the triceps surae were studied by Martin and colleagues (2001).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…This is in stark contrast to findings by Kawakami et al (1998) who reported in vivo ultrasound pennation angles of 31±6° for the LG at MVC, considerably different than the smaller values used by Bogey et al, (2005). The average pennation angle for the male subjects in our study was 22°; identical to the in vivo value reported by Maganaris (2003). Differences between cadaver and in vivo measures of muscle architecture for the triceps surae were studied by Martin and colleagues (2001).…”
Section: Discussioncontrasting
confidence: 92%
“…Muscle fiber length and pennation angle changes with muscle contraction intensity (Maganaris et al, 1998;Maganaris, 2003;Narici et al, 1996). Contractile effort is reflected in the magnitude of the electromyogram (Buchanan et al, 2004), and therefore the EMG signal may be a predictor of fiber length and pennation angle change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method used to estimate muscle forces is calculation of the ratio of the muscular moment about a joint and the moment arm of the muscle or tendon of interest. A number of techniques can be used to obtain muscle moment arms, including cadaver dissection (6,7,11,27), magnetic resonance (MR) imaging (16,26), and ultrasound imaging (9,(12)(13)(14).…”
mentioning
confidence: 99%
“…Isto se dá pelo menor comprimento da bra do GNM, que implica em uma menor amplitude efetiva de produção de torque máximo 23 . O GNL, por outro lado, com bras mais longas, poderia manter níveis su cientes de torque por uma maior variação de comprimento da bra.…”
Section: Resultsunclassified